Análisis de la incidencia de comercialización de su producción, en la situación económica de los pescadores artesanales de la parroquia Posorja del cantón Guayaquil - Valenzuela Galarza, Nathaly Andrea (2016)
Artisanal Fisheries is considered an important source of income for residents of coast areas who dedicate their lives into this activity to support their families; however, the new technological methods in catching fishes put aside the Artisanal fisheries, making significant changes in the living standards of the people who dedicate into it over time. The main objective of this thesis is to understand the factors involved in the commercial process of production of Artisanal Fisheries in Posorja - Guayaquil and analyze the relationship with the economic situation to determine the main inconvenience………